Solitary Fibrous Tumor of the Sigmoid Colon Masquerading as an Adnexal Neoplasm - Laura Bratton; Rabih Salloum; Wenqing Cao; Aaron R. Huber (Case Reports in Pathology)
Solitary fibrous tumor is a rare, benign spindle cell neoplasm that was first described in the thoracic pleura. This tumor is now known to occur at many extrapleural sites. There are established criteria for the diagnosis of malignant solitary fibrous tumor including ≥4 mitotic figures per 10 high-power fields, increased cellularity, cytologic atypia, infiltrative margins, and/or necrosis. Although all solitary fibrous tumors have the potential to recur or metastasize, those with malignant histologic features tend to behave more aggressively. We report a case of solitary fibrous tumor, with malignant histologic features, in a 21-year-old woman which arose from the serosal surface of the sigmoid colon.